ECOLOGICAL-GEOGRAPHICAL FEATURES OF MORBIDITY MALIGNANT NEOPLASMS OF THE POPULATION OF THE CHECHEN REPUBLIC - G. M. Abdurakhmanov; T. N. Ashurbekova (Юг России: экология, развитие)
Presents an analysis of long-term data on cancer incidence of the population of theChechenRepublic. Examines the state of water quality in districts and cities of the Republic to reveal in these areas carcinogenic and carcinogenic factors of the environment.